POLITENESS STRATEGIES OF REFUSALS TO REQUESTS BY AMBONESE COMMUNITY - Azwan Azwan (Center of Language and Cultural Studies, 2018)
The study aims to determine the politeness strategies of refusal used by the Ambonese in refusing requests, and to determine the affects of social relationship towards politeness strategies of refusal used by the Ambonese in refusing requests. The data were taken from 25 respondents of Ambonese in Namlea sub-district, Buru Regency of Maluku Province by recording the conversations in any situation and taking note to remember every little thing that would be happened between the interlocutors. The analysis was conducted by using descriptive qualitative method. The results showed that Ambonese people more likely to combine more than two or three strategies in refusing requests. In the interaction between strangers, Ambonese people tend to use positive politeness strategy such as expressing gratitude which is combined by addressed form, reason and offer new solutions. In solidarity politeness system such as intimate relationship, Ambonese people tend to combine addressed form, reason, promise, joke or offer new solution as sub-strategies of positive politeness strategy. In hierarchical politeness system, Ambonese people tend to use negative politeness strategy such as apology, give deference and be conventionally indirect.